Tackling inflammation in atherosclerosis: Are we there yet and what lies beyond?. (October 2022) - Bhattacharya, Purbasha; Kanagasooriyan, Ragulan; Subramanian, Manikandan
Abstract: Atherosclerosis is a lipid-driven disease of the artery characterized by chronic non-resolving inflammation. Despite availability of excellent lipid-lowering therapies, atherosclerosis remains the leading cause of disability and death globally. The demonstration that suppressing inflammation prevents the adverse clinical manifestations of atherosclerosis in recent clinical trials has led to heightened interest in anti-inflammatory therapies. In this review, we briefly highlight some key anti-inflammatory and pro-resolution pathways, which could be targeted to modulate pathogenesis and stall atherosclerosis progression. We also highlight key challenges that must be overcome to turn the concept of inflammation targeting therapies into clinical reality for atherosclerotic heart disease.